TUBERCULOSIS MASQUERADING AS ENDOBRONCHIAL GROWTH IN YOUNG ADULT FEMALES: TWO CASE REPORTS - ASHFAQ HASAN; KT VIJAYA; SYED MAHMOOD AHMED; TLN SWAMY (International Journal of Pharma and Bio Sciences, 2013)
Tuberculosis has been described in the past as “The Great Mimic”. Despite its protean manifestations, the presentation of tuberculosis as an endobronchial tumor is rare. We present two cases in young adult females with sessile endobronchial tumours that suggested malignancy but yielded a diagnosis of tuberculosis. Both patients responded well to anti-tuberculous treatment with complete radiological resolution.